PEMBUATAN MODEL RENCANA STRATEGI PENGEMBANGAN SI/TI DENGAN ZACHMAN FRAMEWORK - Basir, Azhar; Ishlakhuddin, Fauzan; Akbar, Muhammad Syaeful (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2021)
Organizations need to have IT governance within a certain time frame or commonly referred to as an IT blueprint as a guideline for the organization's strategic planning in designing the needs, development and management of information systems and technology. Sekolah Tinggi Manajemen Informatika dan Komputer (STMIK) Muhammadiyah Paguyangan Brebes is a university that has the view that IS/IT strategic planning is a basic need that can be used to realize the vision and mission. The scope of this research is limited to the academic section (BAA) by dividing the main activities and supporting activities using the value chain, while the enterprise architecture methodology uses the Zachman framework which refers to the first line of the planner's perspective, the second line of the owner's perspective and the data, function and network columns. . This research produces a blueprint for information systems and technology that can be used as a reference in the development of information systems and technology in the 2021-2026 timeframe which has been tested with the results that it is feasible to apply in STMIK-MPB.